2015
DOI: 10.1126/science.aaa7532
|View full text |Cite
|
Sign up to set email alerts
|

Subnanoscale hydrophobic modulation of salt bridges in aqueous media

Abstract: Polar interactions such as electrostatic forces and hydrogen bonds play an essential role in biological molecular recognition. On a protein surface, polar interactions occur mostly in a hydrophobic environment because nonpolar amino acid residues cover ~75% of the protein surface. We report that ionic interactions on a hydrophobic surface are modulated by their subnanoscale distance to the surface. We developed a series of ionic head groups-appended self-assembled monolayers with C2, C6, C8, and C12 space-fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 43 publications
6
62
0
Order By: Relevance
“…Recent experiments have suggested that modifying hydrophobicity could achieve this aim, because hydrophobic interfaces can affect electrostatic binding. 134 We also note that immobilized charged groups on hydrophobic surfaces can tune hydrophobic interactions (Fig. 5c), which could be useful for changing the gel binding of partially hydrophobic solutes such as CAMPs .…”
Section: Interactive Filtersmentioning
confidence: 83%
“…Recent experiments have suggested that modifying hydrophobicity could achieve this aim, because hydrophobic interfaces can affect electrostatic binding. 134 We also note that immobilized charged groups on hydrophobic surfaces can tune hydrophobic interactions (Fig. 5c), which could be useful for changing the gel binding of partially hydrophobic solutes such as CAMPs .…”
Section: Interactive Filtersmentioning
confidence: 83%
“…[35][36][37] GROMACS has also been employed in studying liquid/air and solid/liquid surfaces. [38][39] Considering the solvation environment of water around the metallate and surfactant head group, as shown in the radial distribution functions in Figure 2, we decompose the water molecules in our simulation box into four groups:…”
Section: Figurementioning
confidence: 99%
“…The area-per-molecule densities for Fmoc-SAM C2 qtz and FITC-SAM C2 qtz were 2.3 and 3.1 nm 2 , respectively, which are in fair agreement with each other and also close to those reported previously ( Figure S1). [17] In their dry state, the head groups are supposed to stay in vicinity of the silicon wafer surface. When these SAMs are dipped in water, their hydrophobic surfaces including the fluorescent head groups are immediately hydrated and embedded in a thin hydration layer (Figure 1c, left).…”
Section: Resultsmentioning
confidence: 99%
“…These luminescent groups were tethered via a 1.5-nm-long flexible oligoether chain to a hydrophobic silicon wafer surface, densely covered with paraffinic chains (Figure 1b). [17] With FITC-SAM Cn (n = the number of methylene units in the paraffinic chains; 2, 6, 8, and 12) as model protein surfaces in combination with a polycationic guest, we found that the salt-bridge between them becomes more protonolysis-tolerant as it is formed in closer proximity to the hydrophobic surface. This observation is in accordance with Shellman's theory [18] and also interesting considering the low-permittivity nature of the hydration layer, described above.…”
Section: Introductionmentioning
confidence: 85%